Standing in the breach [compact disc] - Browne, Jackson (Inside Recordings, 2014)
Jackson Browne's fourteenth studio album is a collection of ten moving songs, at turns deeply personal and political, exploring love, hope, and defiance in the face of the advancing uncertainties of modern life.